(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Nuclear radiology has become an indispensable tool in the management of cardiovascular diseases (CVDs), offering unique insights into cardiac structure, function, perfusion, and metabolism. This article provides a comprehensive overview of the pivotal role of nuclear radiology in cardiovascular disease management, focusing on its contributions to diagnosis, risk stratification, and therapeutic decision-making. Key nuclear imaging techniques, including myocardial perfusion imaging (MPI), single-photon emission computed tomography (SPECT), and positron emission tomography (PET), are discussed in the context of their applications in CVD assessment. Additionally, the role of nuclear radiology in evaluating cardiac function, assessing atherosclerosis and plaque vulnerability, and guiding therapeutic interventions is highlighted. Emerging hybrid imaging modalities and molecular imaging techniques are also explored for their potential to enhance diagnostic accuracy and prognostic assessment in patients with CVDs.